2019
DOI: 10.3390/s19040870
|View full text |Cite
|
Sign up to set email alerts
|

Compensation for Process and Temperature Dependency in a CMOS Image Sensor

Abstract: This paper analyzes and compensates for process and temperature dependency among a (Complementary Metal Oxide Semiconductor) CMOS image sensor (CIS) array. Both the analysis and compensation are supported with experimental results on the CIS’s dark current, dark signal non-uniformity (DSNU), and conversion gain (CG). To model and to compensate for process variations, process sensors based on pixel source follower (SF)’s transconductance gm,SF have been proposed to model and to be compared against the measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
3
4
0
Order By: Relevance
“…Presented SF gain measurements showed reverse trend vs. temperature, earlier studies on pixel conversion and column amplifier gains showed same trend [11], then measured normalized PTF gains (DN/e) for both low (LCG) and high (HCG) conversion gains showed the similar temperature trends as depicted in Figure 18.…”
Section: Source Follower and Pixel Transaction Factor Gain Vs Tempersupporting
confidence: 69%
See 2 more Smart Citations
“…Presented SF gain measurements showed reverse trend vs. temperature, earlier studies on pixel conversion and column amplifier gains showed same trend [11], then measured normalized PTF gains (DN/e) for both low (LCG) and high (HCG) conversion gains showed the similar temperature trends as depicted in Figure 18.…”
Section: Source Follower and Pixel Transaction Factor Gain Vs Tempersupporting
confidence: 69%
“…To understand the temperature impact from the shifting pixel parameters such as SF and PTF gains we performed measurements on five sensor sites across a wafer. Temperature dependency of the SF gain was studied before in consumer range from −20 to +80 • C [11], we extended the range to cover entire automotive range from −40 to +200 • C.…”
Section: Source Follower and Pixel Transaction Factor Gain Vs Tempermentioning
confidence: 99%
See 1 more Smart Citation
“…Dash lines are used to mark the noise in electrons, from which the minimum noise 0.17 e − rms at −70 • C is clearly observed. The CG is higher at low temperature, i.e., 352 µV/e − on average at −70 • C versus 340 µV/e − at 25 • C, likely due to the increase of SF gain as a result of mobility increase thus transconductance increase [18]. The increase of SF gain will reduce the Miller capacitance at the FD node due to gate-source overlap, hence the measured CG is higher at −70 • C. However, the read noise reduction at lower temperatures is not only due to increasing CG, but also SF noise reduction, since CG increases~4% but input-referred read noise decreases~15%.…”
Section: Methodsmentioning
confidence: 99%
“…As time increases, the dark current will continue to grow until each pixel is fully charged. In addition, the temperature of the CMOS sensor will also increase the dark current exponentially [35]. To overcome this, the dark current can be drastically reduced by cooling the temperature of the camera sensor.…”
Section: Effects Of Temperature On Dark Currentmentioning
confidence: 99%